Stock trader's almanac 2013 - Hirsch, Jeffrey A. (Almanac investor series., 2013)
A time-tested guide to stock trading market cycles Published every year since 1968, the Stock Trader's Almanac is a practical investment tool with a wealth of information organized in calendar format. Everyone from well-known money managers to savvy traders and investors relies upon this annual resource for its in-depth analyses and insights. The Stock Trader's Almanac 2013 contains essential historical price information on the stock market, provides monthly and daily reminders, and highlights seasonal trading opportunities and dangers. The Stock Trader's Almanac 2013 is packed with timely insights and targeted analysis to help you navigate turbulent markets and beat the odds in the year ahead. This trusted guide combines over a century's worth of data, statistics, and trends along with vital analysis you won't get anywhere else.-Alerts you to little-known market patterns and tendencies to help forecast market trends with accuracy and confidence -An indispensable annual resource, trusted for over 40 years by traders and investors -The data in the Almanac is some of the best in the business For its wealth of information and the authority of its sources, the Stock Trader's Almanac stands alone as the guide to intelligent investing.